2019
DOI: 10.1186/s12981-019-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

Social barriers in accessing care by clients who returned to HIV care after transient loss to follow-up

Abstract: Background People living with HIV (PLHIV) constantly need to address social issues such as the cost of accessing care, stigma, and lack of social support which impacts on their level of adherence to clinic visits or antiretroviral treatment leading to adverse health outcomes. This study examined the social barriers in accessing care by clients who returned to care after transient loss to follow-up. Methods This study was a cross-sectional survey of PLHIV from 99 US CDC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
12
0
2
Order By: Relevance
“…Patients who start ART within seven days after HIV diagnosis were more likely to be at risk for LTFU. In general, same-day patients were at higher risk for LTFU, but the mortality rate was slightly lower in this group [24,49]. According to the results, the number of baseline CD4+ cells did not play a role in LTFU; however, it seems that higher CD4+ cells during treatment was effective in reducing the risk of LTFU [43,50,76].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Patients who start ART within seven days after HIV diagnosis were more likely to be at risk for LTFU. In general, same-day patients were at higher risk for LTFU, but the mortality rate was slightly lower in this group [24,49]. According to the results, the number of baseline CD4+ cells did not play a role in LTFU; however, it seems that higher CD4+ cells during treatment was effective in reducing the risk of LTFU [43,50,76].…”
Section: Discussionmentioning
confidence: 79%
“…Different studies have reported social and economic issues, such as poverty, lack of social support, and community level stigma as important factors in not receiv-ing proper HIV care [61]. Another important factor is the long distance to a medical facility; one of the major problems for patients living far from medical centers is transportation [24,60,77]. In most of the studies reviewed, there was no difference between genders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This should be interpreted with caution, as our study is not population-based and did not include pregnant women who did not enroll in, or have access to the services and support received in PMTCT programs in the nine included states or across the entire country. Several factors occurring throughout the PMTCT cascade including at the interpersonal, community, healthcare facility and policy/governance levels contribute to low access to maternal ART in Nigeria and other African countries [ 34 40 ]. We expect that as lifelong treatment coverage improves in Nigeria, more women living with HIV would have early access, remain adherent and on ART throughout their first and subsequent pregnancies.…”
Section: Discussionmentioning
confidence: 99%